Vivere in campagna lungo la via Appia: l’organizzazione e lo sfruttamento della terra tra IV sec. a.C. e VI sec. d.C. ad Est di Benevento - Santoriello , Alfonso; De Vita, Cristiano Benedetto (O T I V M, 2018)
The Via Appia is one of the most important road axes mentioned both in ancient sources and in recent literature. However, there are still problems on the identification of some sections, especially in the area East of the city of Benevento. The Ancient Appia Landscapes project aim at the reconstruction of the Appian path through its integration in a broader vision that involves the identification of environmental phenomena and settlement dynamics that have determined socio-economic and productive activities. Results have allowed to outline complex scenarios that respond to the transformations of the main centre, from the proto-urban Maluentum to the Latin colony, up to the developments of the Imperial and late antique period. Economic evolution and political choices define in the countryside both original systems of exploitation and new patterns organized on previous infrastructures, thus determining a ‘stratification’ of ancient landscapes still recognizable in the actual rural fabric.